2
$\begingroup$

Here is my attempted approach to prove that the discriminant $\triangle = 4a^3+27b^2$ of an elliptic curve in the form of $y^2 = x^3 + ax +b$ is zero. I have a problem at the end which doesn't bring me to the expected conclusion. Below is the process, please let me know the error in the process. I try to approach this from the definition of non-singularity (part of the definition of an elliptic curve), which is equivalent to the statement: the equation $y^2 = x^3 + ax +b$ is differentiable everywhere on the graph. From that definition, I try to derive the derivative of $y$ in respect to $x$ through implicit differentiation: \begin{align} y^2 &= x^3+ax+b\\ \label{ref1} 2yy' &= 3x^2+a\\ y' &= \frac{3x^2+a}{2y} \end{align} If the graph is singular, then $y'$ does not exist, in other words: \begin{align} 2y &= 0\\ 3x^2+a &\neq 0 \end{align} I replace $y = 0$ in the equation of elliptic curve which yields \begin{equation} 0 \ = \ x^3 + ax + b \end{equation} I apply Cardano's method, who realize that the form could be represented as \begin{equation} (\alpha-\beta)^3 + 3\alpha\beta(\alpha-\beta) = \alpha^3 - \beta^3 \end{equation} in which \begin{align} \alpha\beta &= \frac{a}{3} \\ \alpha^3 - \beta^3 &= -b \end{align} By substituting $\alpha = \frac{a}{3\beta}$ in the second equation from above, I obtain \begin{equation} (\frac{a}{3\beta})^3 - \beta^3 = -b \end{equation} I further simplify this by considering $\beta^3$ as a whole, i.e. \begin{align} \frac{a^3}{27}-\beta^6 &= -b\beta^3\\ (\beta^3)^2 - b\beta^3 -\frac{a^3}{27} &= 0 \end{align} By quadratic formula, \begin{equation} \beta^3 = \frac{b\pm \sqrt{b^2+\frac{4a^3}{27}}}{2} = \frac{b}{2} \pm \sqrt{\frac{b^2}{4}+\frac{a^3}{27}} \end{equation} From $\alpha^3 - \beta^3 = -b$, I get \begin{equation} \alpha^3 = \beta^3 - b = -\frac{b}{2} \pm \sqrt{\frac{b^2}{4}+\frac{a^3}{27}} \end{equation} From $3x^2+a \neq 0$: \begin{equation} 3\left(\left(-\frac{b}{2} \pm \sqrt{\frac{b^2}{4}+\frac{a^3}{27}}\right)^\frac{1}{3} - \left(\frac{b}{2} \pm \sqrt{\frac{b^2}{4}+\frac{a^3}{27}}\right)^\frac{1}{3}\right)^2 + a \neq0 \end{equation} The equation above is from $3(\alpha-\beta)^2+a \neq 0$. By De Moivre's Formula there are two other equations, $3\left(\alpha(\frac{-1}{2}+\frac{\sqrt{3}i}{2})-\beta(\frac{-1}{2}+\frac{\sqrt{3}i}{2})\right)^2+a \neq 0$ and $3\left(\alpha(\frac{-1}{2}+\frac{\sqrt{3}i}{2})^2-\beta(\frac{-1}{2}+\frac{\sqrt{3}i}{2})\right)^2+a \neq 0$. These result in several representations of b in terms of a and one integer solution, $a=0,b=0$ shouldn't exist at the same time, $b\neq\pm \frac{2ia^{3/2}}{3\sqrt{3}}$. These two meet my expectation, $\triangle = 0$. However, there are other four representations that do not meet my expectation $b \neq \pm \sqrt{\frac{a^3}{54}\pm\frac{5ia^3}{6\sqrt{3}}}$ and $b \neq \pm \sqrt{\frac{a^3}{54}\mp\frac{5ia^3}{6\sqrt{3}}}$. I also try to see what I could get from \begin{equation} 3\left(\left(-\frac{b}{2}\right)^\frac{1}{3} - \left(\frac{b}{2}\right)^\frac{1}{3}\right)^2 + a \neq0 \end{equation} which yields that $a=0,b=0$ shouldn't exist at the same time, or $b\neq\pm \frac{2ia^{3/2}}{3\sqrt{3}}$ these satisfy $\triangle = 0$ and also a weird pair of $b \neq \pm \frac{ia^{3/2}}{12\sqrt{3}}$, which doesn't even satisfy $\triangle = 0$. Could someone explain this?

$\endgroup$

1 Answer 1

2
$\begingroup$

When $3x^2 + a \ne0$ and $2y = 0$, the curve is still nonsingular, its just that the slope of the tangent line is infinite. The singularity occurs when $$3x^2 + a = 0 \text{ and } 2y =0$$ simultaneously i.e. $a = - 3x^2$ so $0 = x^3 + (-3x^2)x + b$ giving $$ b = 2x^3$$ this is what leads to the equation $$27b^2 + 4a^3 = 0$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.